The effect of environment on the formation and evolution of galaxies in the distant universe - Chuter, Robert W. (2011)
In this thesis I primarily use the UKIDSS Ultra-Deep Survey (UDS) to investigate the effect environment has on galaxies across the redshift range 0.25 < z < 3.25. The UDS is a K-selected survey so it does not suffer from the strong iases that affect optical surveys at high redshift (z > 1). The combination of a large contiguous area (0.77 deg2) and depth (KAB ∼24) allows us to study a range of environments up to a redshift of z ∼3. Due to the multiwavelength coverage we are able to obtain reliable photometric redshifts which are necessary for studies of environment. I utilise progressive releases of the UDS data to study the effect environment has on the rest frame (U-B) colour of galaxies. Using the U-B colour and absolute K-band magnitude I was able to divide our galaxies into red and blue and study their average environments. In this thesis I also employ data from the spaced based, GOODS NICMOS Survey (GNS) to help study the environments out to high redshift (z ∼3), in which I also study the colour-density relation.